Resistance training among young athletes: safety, efficacy and injury prevention effects - Faigenbaum, A. D.; Myer, G. D. (British Journal of Sports Medicine, 2010)
A literature review was employed to evaluate the current epidemiology of injury related to the safety and efficacy of youth resistance training. Several case study reports and retrospective questionnaires regarding resistance exercise and the competitive sports of weightlifting and powerlifting reveal that injuries have occurred in young lifters, although a majority can be classified as accidental. Lack of qualified instruction that underlies poor exercise technique and inappropriate training loads could explain, at least partly, some of the reported injuries. Current research indicates that resistance training can be a safe, effective and worthwhile activity for children and adolescents provided that qualified professionals supervise all training sessions and provide age-appropriate instruction on proper lifting procedures and safe training guidelines. Regular participation in a multifaceted resistance training programme that begins during the preseason and includes instruction on movement biomechanics may reduce the risk of sports-related injuries in young athletes. Strategies for enhancing the safety of youth resistance training are discussed.